Diagnostic work-up and phenotypic characteristics of a family with variable severity of distal arthrogryposis type 2B (Sheldon-Hall syndrome) and TNNT3 pathogenic variant - Dabaj, Ivana; Carlier, Robert Y.; Dieterich, Klaus; Desguerre, Isabelle; Faure, Julien; Romero, Norma B.; Trang, Wenting; Quijano-Roy, Susana; Germain, Dominique P. (Frontiers in Genetics, 2023)
Background: Sheldon–Hall syndrome (SHS) or distal arthrogryposis 2B (DA2B) is a rare clinically and genetically heterogeneous multiple congenital contracture syndrome characterized by contractures of the distal joints of the limbs and mild facial involvement, due to pathogenic variants in genes encoding the fast-twitch skeletal muscle contractile myofiber complex (TNNT3, TNNI2, TMP2, and MYH3 genes). Patients and methods: A 16-year-old boy with a history of congenital distal arthrogryposis developed severe kyphoscoliosis and respiratory insufficiency. His mother and younger sister had phenotypes compatible with SHS but to a much lesser extent. Diagnostic work-up included physical examination and whole-body muscular MRI (WBMRI) in all three patients and electroneuromyography (ENMG) and paravertebral muscle biopsy in the proband. DNA sequencing was used to confirm the diagnosis. Results: Physical examination suggested the diagnosis of SHS. No muscle signal abnormalities were found in WBMRI. Large motor unit potentials and reduced recruitment suggestive of neurogenic changes were observed on needle EMG in distal and paravertebral muscles in the proband. DNA sequencing revealed a pathogenic variant in TNNT3 (c.187C>T), which segregated as a dominant trait with the phenotype. Discussion: This is the first report on neurogenic features in a patient with DA2B and a pathogenic variant in TNNT3 encoding the fast-twitch skeletal muscle contractile myofiber complex. A superimposed length-dependent motor nerve involvement was unexpected. Whether developmental disarrangements in number, distribution, or innervation of the motor unit in fetal life might lead to pseudo-neurogenic EMG features warrants further studies, as well as the role of genetic modifiers in SHS variability.